2021
DOI: 10.1371/journal.pone.0258105
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of depression, anxiety, and stress among adults in Ghana: A community-based cross-sectional study

Abstract: Introduction Over the past two decades, there have been several global interventions including the Sustainable Development Goals (SDGs), aimed at improving health outcomes. Despite efforts by countries to achieve the SDG targets, mental health challenges remain major public health concerns globally. We examined the prevalence and predictors of depression, anxiety, and stress as well as the comorbidities of these mental health issues among adults. Materials and methods This was a community-based cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 53 publications
4
16
0
Order By: Relevance
“…This difference may be because this study was executed after these aforementioned investigations; hence, there may have been understandable improvements in the psychological health of healthcare workers over time. Of note, the prevalence of all three symptoms (8%) among Chinese psychiatrists who specialize in interventions for individuals with mental illness in this study was similar to that of the general population in at least one other country (Ghana) (8.3%) (Amu et al, 2021 ), suggesting that caring for this patient population may be detrimental to the mental health and wellbeing of psychiatrists. Such a high prevalence of mental health symptoms among Chinese psychiatrists means that more easily accessible and uniquely tailored healthcare services should be provided to this population.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This difference may be because this study was executed after these aforementioned investigations; hence, there may have been understandable improvements in the psychological health of healthcare workers over time. Of note, the prevalence of all three symptoms (8%) among Chinese psychiatrists who specialize in interventions for individuals with mental illness in this study was similar to that of the general population in at least one other country (Ghana) (8.3%) (Amu et al, 2021 ), suggesting that caring for this patient population may be detrimental to the mental health and wellbeing of psychiatrists. Such a high prevalence of mental health symptoms among Chinese psychiatrists means that more easily accessible and uniquely tailored healthcare services should be provided to this population.…”
Section: Discussionsupporting
confidence: 61%
“…Binary logistic regression models (univariable and multivariable) were used to investigate the independent risk factors associated with depressive, anxious, and stress symptoms. In a multivariable logistic regression model, mental health problems (such as depressive, anxious, and stress symptoms) were the dependent variables, and the covariates were the variables that showed significant differences ( P < 0.2) between the depression/no-depression, anxiety/no-anxiety, and stress/no-stress groups in the univariable analysis (Amu et al, 2021 ). The independent associations of depressive, anxious, and stress symptoms and their interaction with QOL were analyzed using multivariate analysis of covariance (MANOVA) after controlling for variables with striking group differences in univariable analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Our study found associations between severe mental illness like psychosis and depression. This is consistent with previous studies that have reported psychiatric comorbidities among patients with schizophrenia including depression and anxiety disorders (41,55,56), with depression co-occurring in persons within first episode psychosis (55).…”
Section: Correlates Of Mns Conditionssupporting
confidence: 93%
“…An overall prevalence of depression among the study participants was 15.6%. This prevalence compares with previous studies in Ghana that reported depression prevalence in the range of 25% to 62% (38)(39)(40)(41). We observed a marginally higher prevalence of depression in men than in women in the whole sample.…”
Section: Prevalence Of Priority Mnssupporting
confidence: 61%
“…*Globally, in the face of the growing threat from the new variants of the coronavirus , it has been reported at the public health level that the general population has increased rates of depression, anxiety, and stress (Amu et al, 2021). So, the infection rates for the new variant are increasing and this increases different psycho-emotional signs in each of the people (Alnazly et al, 2021;Li et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%